2020
DOI: 10.1001/jamaoncol.2020.4759
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Integrating Machine Learning Mortality Estimates With Behavioral Nudges to Clinicians on Serious Illness Conversations Among Patients With Cancer

Abstract: IMPORTANCE Serious illness conversations (SICs) are structured conversations between clinicians and patients about prognosis, treatment goals, and end-of-life preferences. Interventions that increase the rate of SICs between oncology clinicians and patients may improve goal-concordant care and patient outcomes. OBJECTIVE To determine the effect of a clinician-directed intervention integrating machine learning mortality predictions with behavioral nudges on motivating clinician-patient SICs. DESIGN, SETTING, AN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
172
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 127 publications
(177 citation statements)
references
References 40 publications
5
172
0
Order By: Relevance
“…Future studies can refine on decision analysis based on this retroactive feedback, like including model-independent effects from behavioural economic–inspired co-interventions. [47]…”
Section: Discussionmentioning
confidence: 99%
“…Future studies can refine on decision analysis based on this retroactive feedback, like including model-independent effects from behavioural economic–inspired co-interventions. [47]…”
Section: Discussionmentioning
confidence: 99%
“…24 For example, using an 'opt-out' approach for palliative care referral may make the optimal choice the path of least resistance, increasing uptake among clinicians. 16 These approaches will need to be balanced against rising clinician alert fatigue 25 and resource constraints.…”
mentioning
confidence: 99%
“…Prognostic inaccuracy among clinicians contributes to low-quality EOL care, including delayed hospice utilization and increased acute care utilization close to death, for patients with serious illnesses, such as cancer 3 , 4 . Machine learning (ML) algorithms outperform traditional tools used for prognostication and may facilitate earlier clinician–patient discussions about hospice enrollment, discontinuation of therapy, or other management decisions 5 . Most research to date has reported on the performance of static predictions of mortality risk from ML algorithms 5 7 .…”
mentioning
confidence: 99%
“…Machine learning (ML) algorithms outperform traditional tools used for prognostication and may facilitate earlier clinician–patient discussions about hospice enrollment, discontinuation of therapy, or other management decisions 5 . Most research to date has reported on the performance of static predictions of mortality risk from ML algorithms 5 7 . However, patients’ risk of mortality may change over time in non-linear patterns.…”
mentioning
confidence: 99%
See 1 more Smart Citation